Examining the Multifaceted Determinants of Antenatal Care Utilization in Ghana Using Structural Equation Modelling - Sam, Napoleon Bellua; Aboyine, Thomas; Tackie-Otoo, Theresah (European Scientific Journal, ESJ, 2024)
Introductions: Maternal and newborn mortality remains a critical global public health challenge, especially in middle- and lower-income countries. One of the most effective strategies for reducing these mortality rates is the adequate utilization of antenatal care (ANC). This study investigated the determinants influencing ANC utilization and aimed to predict the demographic characteristics that impact ANC attendance using Structural Equation Modelling (SEM). Methods: A cross-sectional analytical study was conducted with 254 pregnant women at St. Lucas Hospital in Ghana. Data were collected using a structured questionnaire. SEM and Chi-square analysis were employed to model and examine the determinants influencing antenatal care utilization. Results: The findings revealed that the majority (72%) of postpartum mothers had four or more ANC contacts during their most recent pregnancy, with 47.6% initiating ANC attendance in the first trimester. ANC usage was significantly associated with maternal education level (P = 0.000), occupational status (P = 0.000), age (P = 0.030), marital status (P = 0.034), religious affiliation (P = 0.000), husband’s education (P = 0.000), and husband’s occupation (P = 0.000).. Furthermore, SEM analysis showed that community factors (P = 0.005) and health provider factors (P = 0.000) were important in ANC utilization. This study identified significant demographic factors, such as maternal and husband’s education and occupation, and highlighted the critical roles of health providers and community factors in ANC utilization. Conclusions: This study established some essential determinants such as health provider and community factors in the utilization of ANC contacts. The study also revealed some demographic characteristics as crucial determinants of ANC attendance.